Model for Long-Term Partnerships Between the Government and Subsoil Users in Production and Infrastructure Construction - Lavlinskii, Sergey; Zyryanov, Alexander (2023 19th International Asian School-Seminar on Optimization Problems of Complex Systems (OPCS), 2023)
This paper explores a model of partnership between the state and private investors based on the clustering of fields and the creation of a system of consortia of private investors who jointly implement projects to build the necessary production infrastructure. This mechanism is based on a Stackelberg equilibrium search. The results of calculations based on real data of Zabaikalsky Krai allow us to formulate several practical recommendations on the formation of the equity construction mechanism and compensation policy. It is shown that the liberal investment policy of the state as a partner of the consortium system, to the greatest extent ensures the interests of both the budget and the private investor. The transition of the state to a conservative investment policy can be justified only in conditions of extremely tight budget constraints. The consequences of such a policy in Russian conditions lead to a reduction in the front of production and infrastructure construction and, as a consequence, discourage the entry of private investors into the underdeveloped raw material territory.